AN ANALYSIS OF COMMUNICATION STRATEGIES USED IN NGIDIH WEDDING CEREMONY IN SAWAN VILLAGE - ., Made Arniati; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin; ., Dewa Putu Ramendra, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujian untuk: (1) mendeskripsikan langakah langkah pada perkawinan Ngidih di desa Sawan, (2) mendeskripsikan jenis jenis strategi berkomunikasi yang digunakan oleh Prajuru ‘kepala desa, klian desa adat, dan delegasi dari keluarga laki-laki’, dalam perkawinan Ngidih di desa Sawan, (3) mengivestigasi alasan dari Prajuru ‘kepala desa, klian desa adat, dan delegasi dari keluarga laki-laki’ dalam menggunakan strategi berkomunikasi pada perkawinan Ngidih di desa Sawan. Bentuk penelitian ini adalah deskriptip. Data yang diperoleh dianalisis dengan cara deskripsi. Subjek dari penelitian ini adalah lima orang yang terlibat dalam perkawinan Ngidih di desa Sawan. Berdasarkan penelitian dapat disimpulkan bahwa ada delapan langkah-langkah dalam perkawinan Ngidih di desa Sawan, diantaranya: Ngeluku ‘perkenalan keluarga mempelai laki laki dan perempuan’, Nyedekang/ Meparisedek ‘penentuan hari meminta mempelai perempuan, Ngidih ‘meminta mempelai perempuan untuk dibawa kerumah mempelai laki laki’ Pebiayakala ‘penyucian mempelai laki laki dan perempuan’, Mesakapan/Medengenan ‘penyatuan mempelai laki laki dan perempuan’ , Medapetan ‘pengesahan perkawinan’, Mepedambel ‘menjelaskan berbagai rasa dalam hidup’, and Ngelaliang ‘berkunjung ke rumah mempelai perempuan’. Berdsarkan hasil penelitian maka ditemukan bahwa ada lima jenis strategi berkomunikasi yang digunakan oleh Prajuru ‘kepala desa, klian desa adat, dan delegasi dari keluarga laki-laki’, diantaranya: approximation, circumlocution, language switching, paralanguage, dan clarification request. Alasan mereka menggunkan strategi berkomunikasi, diantaranya: untuk mengidari kesalahpahaman/ membuat pendengar mengerti, memberikan penjelasan yang baik, dan menekankan ucapan ucapan. Kata Kunci : strategi berkomunikasi, perkawinan This study aimed at (1) describing the procedures in Ngidih wedding in Sawan village, (2) describing the types of communication strategies used by Prajuru ‘the head of the village, the village head of culture and tradition, and the groom’s delegation’ in ngidih wedding in Sawan village, (3) investigating the reasons of Prajuru ‘the head of the village, the head culture and tradition of village, and the groom’s delegation’ in applying the communication strategies during Ngidih wedding in Sawan village. This study was designed in the form of qualitative research. The obtained data were analyzed descriptively. The subjects of this study were five people who were involved in Ngidih wedding in Sawan village. It was found that they were several procedures of Ngidih wedding in Sawan village which included: Ngeluku ‘Introducing the family member of the groom’s family to the bride’s family’, Nyedekang/ Meparisedek ‘Determining the date of Ngidih wedding ceremony’, Ngidih ‘Asking the bride to the groom’s house’, Pebiayakala ‘Purification of the groom and the bride arriving in groom’s house’, Mesakapan/Medengenan ‘Uniting the groom and bride’, Medapetan ‘Legalizing the marriage’, Mepedambel ‘Explaining the taste of life’, and Ngelaliang ‘Visiting the groom’s house’. The results of the analysis show that the Prajuru ‘the head of the village, the head culture and tradition of village, and the groom’s delegation’ used six types of communication strategies which included: approximation, circumlocution, language switching, paralanguage, and clarification request. Their reasons to use the communication strategies were to avoid misunderstanding/ make the listeners understand, to give brief explanation, and to emphasize the utterances. keyword : This study aimed at (1) describing the procedures in Ngidih wedding in Sawan village, (2) describing the types of communication strategies used by Prajuru ‘the head of the village, the village head of culture and tradition, and the groom’s delegation’ in ngidih wedding in Sawan village, (3) investigating the reasons of Prajuru ‘the head of the village, the head culture and tradition of village, and the groom’s delegation’ in applying the communication strategies during Ngidih wedding in Sawan village. This study was designed in the form of qualitative research. The obtained data were analyzed descriptively. The subjects of this study were five people who were involved in Ngidih wedding in Sawan village. It was found that they were several procedures of Ngidih wedding in Sawan village which included: Ngeluku ‘Introducing the family member of the groom’s family to the bride’s family’, Nyedekang/ Meparisedek ‘Determining the date of Ngidih wedding ceremony’, Ngidih ‘Asking the bride to the groom’s house’, Pebiayakala ‘Purification of the groom and the bride arriving in groom’s house’, Mesakapan/Medengenan ‘Uniting the groom and bride’, Medapetan ‘Legalizing the marriage’, Mepedambel ‘Explaining the taste of life’, and Ngelaliang ‘Visiting the groom’s house’. The results of the analysis show that the Prajuru ‘the head of the village, the head culture and tradition of village, and the groom’s delegation’ used six types of communication strategies which included: approximation, circumlocution, language switching, paralanguage, and clarification request. Their reasons to use the communication strategies were to avoid misunderstanding/ make the listeners understand, to give brief explanation, and to emphasize the utterances.